APPLICATION OF A REALISTIC MATHEMATICAL APPROACH TO IMPROVE THE CAPACITY OF THE PROBLEM MATHEMATIC STUDENTS CLASS VII SMP NEGERI 3 SATU ATAP KUALA - Elva . Bonica; Hasratuddin . . (Universitas Negeri Medan, 2018)
ABSTRACT The purpose of this research is to know the improvement of students' mathematical problem solving ability after applying realistic mathematics approach of class VII-b SMP Negeri 3 Satu Atap Kuala and to describe that realistic mathematics approach is better than conventional learning. The subjects of the study were Class VII-b SMP Negeri 3 Satu Atap Kuala which amounted to 40 students. The object of this research is to improve students' mathematical problem solving ability through realistic mathematics approach class VII-b SMP Negeri 3 Satu Atap Kuala. This type of research is a classroom action research. In this study consists of two cycles, where at the end of each cycle is given a problem-solving test to determine students' mathematical problem solving abilities. The question form for each test is a description. The first procedure in this study was to give an initial skill test to class VII-b (to be studied) and class VII-a, in order to see students' early mathematical problem-solving abilities. The two held a lesson with the application of a realistic mathematical approach with rectangular subjects in class VII-b. Before the first action is given a preliminary test to determine the initial ability and early difficulty of students. From the preliminary results of the tests, the mean grade of grade VII-b is 53.75 and class VII-a is 53.625. After giving the action through realistic mathematics approach in cycle 1 in class VII-b, the mean value of problem solving ability test I was 70.83 with the number of students who have reached the classical learning completeness level of 24 students (60%) and conventional class VII -a is 60.17 with the number of students reaching the classical learning level of 9 students (22.5%). While after the improvement of cycle I in cycle II, the average value of problem solving test of class II VII-b is 81.83 with the number of students reaching the classical learning level of 37 students (92,5%) and class VII-a is 69.08 with the number of students reaching the classical learning level as much as 19 students (47,5%). Based on the results of this study indicate that by applying realistic mathematics approach on rectangular subjects in class VII-b SMP Negeri 3 Satu Atap Kuala can improve the problem solving ability of mathematical students and classes that are given a realistic mathematical learning approach is better than the class that is given conventional learning .Keywords: Problem Solving Abilities, Realistic Mathematical Approach ABSTRAKTujuan penelitian ini adalah untuk mengetahui peningkatan kemampuan pemecahan masalah matematis siswa setelah diterapkan pendekatan matematika realistik kelas VII-b SMP Negeri 3 Satu Atap Kuala dan untuk mendeskripsikan bahwa pendekatan matematika realistik lebih baik daripada pembelajaran konvensional. Subjek penelitian adalah kelas VII-b SMP Negeri 3 Satu Atap Kuala yang berjumlah 40 siswa. Objek penelitian ini adalah untuk meningkatkan kemampuan pemecahan masalah matematis siswa melalui pendekatan matematika realistik kelas VII-b SMP Negeri 3 Satu Atap Kuala T.A 2016/2017. Jenis penelitian ini adalah penelitian tindakan kelas. Dalam penelitian ini terdiri dari dua siklus, dimana di akhir setiap siklus diberikan tes kemampuan pemecahan masalah untuk mengetahui kemampuan pemecahan masalah matematis siswa. Bentuk soal untuk setiap tes adalah uraian. Prosedur yang pertama pada penelitian ini adalah memberi tes kemampuan awal kepada kelas VII-b (yang akan diteliti) dan kelas VII-a, guna untuk melihat kemampuan pemecahan masalah matematis awal siswa. Kedua mengadakan pembelajaran dengan penerapan pendekatan matematika realistik dengan pokok bahasan segi empat di kelas VII-b. Sebelum tindakan dilakukan terlebih dahulu diberikan tes awal untuk mengetahui kemampuan awal dan kesulitan awal siswa. Dari hasil tes awal yag diperoleh menunjukkan bahwa nilai rata – rata kelas VII-b adalah 53,75 dan kelas VII-a adalah 53,625. Setelah pemberian tindakan melalui pendekatan matematika realistik pada siklus 1 di kelas VII-b, nilai rata – rata tes kemampuan pemecahan masalah I adalah 70,83 dengan jumlah siswa yang telah mencapai tingkat ketuntasan belajar klasikal sebanyak 24 siswa (60%) dan kelas konvensional VII-a adalah 60,17 dengan jumlah siswa yang mencapai tingkat belajar klasikal sebanyak 9 siswa (22,5%). Sedangkan setelah dilakukan perbaikan dari siklus I pada siklus II, nilai rata – rata tes kemampuan pemecahan masalah II kelas VII-b adalah 81,83 dengan jumlah siswa yang mencapai tingkat belajar klasikal sebanyak 37 siswa (92,5%) dan kelas VII-a adalah 69,08 dengan jumlah siswa yang mencapai tingkat belajar klasikal sebanyak 19 siswa (47,5%). Berdasarkan hasil penelitian ini menunjukkan bahwa dengan menerapkan pendekatan matematika realistik pada pokok bahasan segi empat di kelas VII-b SMP Negeri 3 Satu Atap Kuala dapat meningkatkan kemampuan pemecahan masalah matematis siswa dan kelas yang diberi pembelajaran pendekatan matematika realistik lebih baik daripada kelas yang diberi pembelajaran konvensional.Kata Kunci : Kemampuan Pemecahan Masalah, Pendekatan Matematika Realistik